Pengaruh Kompensasi Terhadap Produktivitas Kerja Dengan Kepuasan Kerja Sebagai Variabel Mediasi: Studi Pada Karyawan Griya Motor Group - Daffa Muhammad Alfaiq; Indi Djastuti (Faculty of Economics and Business Diponegoro University, 2025)
This research aims to find out: (1) Can compensation directly influences work productivity in Griya Motor Group? (2) Can compensation directly influences job satisfaction in Griya Motor Group? (3) Can the influences of compensation on work productivity are mediated by job satisfaction in Griya Motor Group? This research uses a quantitative approach with a focus on causal associations. The population studied was all employees at Griya Motor Group, totaling 100 people. Data was collected by using a questionnaire whose validity and reliability had been verified. The data analysis method used to test this research hypothesis is path analysis. The data that has been collected is analyzed using the Partial Least Square (PLS) method using the SmartPLS application version 4. The purpose of this analysis is to test the hypothesis and measure the influence of the relationship between variables. The results of this research indicate that compensation has a positive and significant influence on work productivity and a positive and significant influence on job satisfaction. Job satisfaction also has a positive and significant effect on work productivity. The findings in this study also confirm that job satisfaction acts as an important mediating variable in the relationship between compensation and work productivity. This research also provides a valuable contribution in the theoretical and managerial context regarding appropriate strategies for developing compensation and job satisfaction to support, encourage, and increase work productivity among employees of the Griya Motor Group.